Dimensions of impact in the social sciences : the case of social policy, sociology and political science research - Haux, Tina (Policy Press shorts. Research., 2019)
This concise, informative book analyses impact across the social sciences. Drawing on fifteen interviews with senior academics for a longitudinal view, the author sets out valuable recommendations of how and when scholars can achieve impact.